Christine Moore-Bonbright: capstone - Moore-Bonbright, Christine, artist (Colorado State University. Libraries, 2022)
The artist's statement: I once believed that fine art and graphic design were two separate worlds, with the former in galleries and museums and the latter in advertisements and magazines. Yet as I immersed myself into both worlds during my college career, I realized that this notion is untrue. Fine artists and designers share many values and art practices. Just as fine artists utilize fundamental art principles like color and scale to convey their messages, graphic designers employ the same principles to convey theirs. And perhaps the most important connection is that the two fields have the same fundamental goal: to tell a story. My design practice reflects the increasing convergence of fine art and graphic design, centralizing me in the role of the storyteller. I experiment with analog and digital materials, and I push the fundamentals of art and design. I am a designer as much as I am a fine artist. And those two facets of my artistic identity need not be separate from one another.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design